Knowledge on and Attitude toward Silver Diamine Fluoride among Saudi Dental Practitioners in Riyadh Public Hospitals - Alajlan G; Alshaikh H; Alshamrani L; Alanezi M; Alarfaj S; AlSwayyed T (Dove Medical Press, 2020)
Ghadah Alajlan,1,* Hessa Alshaikh,2,3,* Lamar Alshamrani,1,* Malak Alanezi,4,* Salma Alarfaj,5,* Tariq AlSwayyed3,6 1Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 2King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 3King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 4Buraydah Private Colleges, Qassim, Saudi Arabia; 5Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 6King Abduaziz Medical City/King Saud Bin Abdulaziz University for Health Sciences, Ministry of National Guard, Riyadh, Saudi Arabia*These authors contributed equally to this workCorrespondence: Tariq AlSwayyedKing Abduaziz Medical City/King Saud Bin Abdulaziz University for Health Sciences, Ministry of National Guard, Riyadh 11426, Saudi ArabiaTel +966554428965Email tariqss1@yahoo.comAim: This study assessed the knowledge on and attitude toward silver diamine fluoride among Saudi dental practitioners in Riyadh public hospitals.Materials and Methods: A cross-sectional study was done, data were collected between July and October 2019 using a validated, and the published questionnaire was analyzed. A sample size of 278 public hospital dental practitioners in Riyadh, Saudi Arabia, was used. Participants who agreed to the study completed a 3-section questionnaire of Likert scale comprising multiple questions regarding demographic data, knowledge on silver diamine fluoride, potential, and actual use of SDF in dental practitioner’s own professional life. Finally, respondents were asked about the future usage of SDF.Results: A total of 278 Saudi dentists in Riyadh public hospitals completed the survey. The mean knowledge of SDF among participants was averagely 3.1. About half of the participants (50.4%) agreed that SDF could be used to arrest cavitated lesions. The majority of respondents showed a positive attitude toward SDF by accepting it as a good alternative treatment for individuals with behavioral problems or medical issues (> 50%). The most frequently reported barrier to the use of SDF was black discoloration (55.39%). A high number of respondents have not experienced the application of SDF, in their practice (> 60%), or dental school (65.5%). However, 57.9% expect an increase in the future use of SDF. The correlation between knowledge and attitude among different dental specialties was statistically significant (P< 0.05). The restorative specialty was observed to have the highest mean of knowledge (3.26), while advanced education general dentistry had the highest mean (3.67) of attitude toward SDF.Conclusion: The aim of the study was achieved as the knowledge on, and attitude toward silver diamine fluoride among Saudi dental practitioners in Riyadh public hospitals was assessed. The response was average, with means of 3.1 and 3.3 for knowledge and attitude, respectively, among the participants.Keywords: silver diamine fluoride, dental caries, public hospitals, knowledge, attitude, SDF approval and future usage